Pengaruh Pemberian Irisan Bawang Merah Terhadap Perkecambahan Dan Fase Awal Pertumbuhan Tanaman Jagung ( Zea Mays) - Krisnawati Zega (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to determine the effect of red onion slices on the acceleration of corn seed germination (Zea mays L.). Red onions are known to contain natural phytohormones such as auxin and gibberellin, which can stimulate germination. The research was conducted experimentally with two treatments: corn seeds soaked in water from red onion slices and a control group without treatment. The results showed that seeds treated with red onion water germinated faster, had a higher germination rate, and longer seedling length compared to the control. This indicates that red onion has potential as a natural growth stimulant in corn cultivation.